Royalism, romance, and history in Boscobel: Or, the history of his sacred majesties most miraculous preservation - Turner, Dorothy (My University, 1999)
Boscobel played a changing part in the factional negotiations extending from Charles II's permanent return to England in 1660 through the crises of popery and arbitrary government of the late 1670s. The tract covered wide ideological ground in the later seventeenth century and beyond. While serving variously as early record of accounts due, anti-Presbyterian history, and Catholic apology, it participated continuously in the reaffirmation of Stuart hegemony. Its early publication history serves as a reminder of the shifting boundaries between history and fiction, since its flexibility of function as propaganda, romance, history, and mythology situates the text in the generic flux which marks the emergence of the novel.